Spotkanie Gadamera z Derridą – spojrzenie pragmatysty - Shusterman, Richard (Przestrzenie Teorii, 2016)
The paper offers a philosophical commentary on the widely discussed 1981 meeting of Derrida and Gadamer at Paris’ Goethe Institute. These two figures “virtually personify, in hermeneutics and deconstruction, the two major and rival ‘schools’ of contemporary continental philosophy associated with the primacy of interpretation.” Adopting a pragmatist perspective, the author discusses their approaches to the issue of interpretation – different and often seen as mutually exclusive. He claims that Derrida and Gadamer in fact have a great deal in common and tries to show that American pragmatism offers a mode of mediation, which allows us to grasp their mutual relations. The author concentrates on the three central issues that emerge from Derrida’s Three Questions to Hans-Georg Gadamer, namely the context of interpretation, consensual continuity versus rupture as the basis or precondition of interpretation, and the nature or possibility of perfect dialogical understanding.